An Overview of Peoples Behavior with a History Covid-19 at the Bukit Wolio Indah Health Center - Ni’ma Meilani; Eky Endriana Amiruddin; Apriliani Anastasia Kaligis (PT FORMOSA CENDEKIA GLOBAL, 2023)
Public behavior in dealing with the covid-19 pandemic is of particular concern. Because it has a significant impact on the incidence of covid-19 in the community. These behaviors include knowledge, attitudes and actions. From the observations I made in the working area of the Bukit Wolio Indah Health Center there are still many people who do not comply with health protocols such as the use of masks, and do not keep their distance. The purpose of this study was to obtain an overview and information on the behavior of people with a history of covid-19 in the Bukit Wolio Indah Community Health Center working area. The type of research used is quantitative research with analytical description design. Conducted in June - July 2022. The data used are primary data and secondary data. The number of samples is 26 and the sample is taken by total sampling technique. Presentation and processing of data with the application of Statistical Product and Service Solutions (SPSS) with univariate analysis. The results showed that there were 22 respondents (84.6%) good knowledge and 4 respondents (15.4%) poor knowledge, 15 respondents (57.7%) good attitudes and 11 respondents (42.3%) unfavorable attitudes. ) ) and good actions as many as 26 respondents (100%). The conclusion of this study is that people with a history of covid-19 have sufficient knowledge and attitudes and have good actions about covid-19